Pemetaan Ketimpangan Digital Antarprovinsi di Indonesia Berdasarkan Indikator Akses dan Penggunaan Teknologi Menggunakan Algoritma K-Means - Ulfa Pauziah (INDO PUBLISHING, 2026)
Digital inequality remains a challenge in ensuring equitable access to and use of information and communication technology across regions in Indonesia. This study aimed to map digital inequality among 38 Indonesian provinces in 2024 using the K-Means clustering algorithm. Secondary data obtained from Statistics Indonesia (BPS) were analyzed using three indicators: the percentage of the population accessing the internet, owning or controlling mobile phones, and using computers. The data were standardized using Z-score transformation, while the optimal number of clusters was evaluated using the Elbow Method and Silhouette Score. The results showed that two clusters provided the optimal configuration, with a Silhouette Score of 0.7457. Cluster 0 consisted of 36 provinces, with average internet access, mobile phone ownership or control, and computer use of 70.84%, 69.08%, and 12.09%, respectively. Cluster 1 consisted of Central Papua and Highland Papua, with substantially lower averages of 17.74%, 24.73%, and 2.98%, respectively. Principal Component Analysis further supported the clustering structure, with two principal components explaining 98.89% of the total variance. These findings demonstrate a pronounced multidimensional digital gap and highlight the need for more targeted digital development policies in disadvantaged regions.